The Role of Adjuvant Radiotherapy for the Prevention of Recurrent Hypertrophic Scars/Keloids: An American Radium Society (ARS) Appropriate Use Criteria (AUC) - Suzanne Russo; Corinne Wee; Samuel Jean-Baptiste; Austin N. Kirschner; Bobby Koneru; Christien Kluwe; Diane C. Ling; Neil Newman; Kevin Pearlstein; Yasamin Sharifzadeh; Rahul Tendulkar; Austin Dove (American Journal of Clinical Oncology, 2026)
Objectives: To summarize the evidence for adjuvant radiation therapy (RT) in the prevention of recurrent hypertrophic scars and keloids, including patient selection, optimal RT technique, and associated risks. Methods: This multi-specialty–led committee includes radiation oncology, plastic surgery, and dermatology physicians. Using the Population, Intervention, Comparator, Outcome, Timing, and Study Design (PICOTS) framework, evidence regarding treatment outcomes was assessed using Cochrane and PRISMA methodology. Eligible studies included prospective and retrospective studies published between January 1, 1980 and November 5, 2026, from the Ovid Medline database. Of the 165 articles identified using the search strategy, 87 were selected for inclusion as evidence, including 3 well-designed studies (phase II randomized and phase III), 23 moderately well-designed studies that account for most common biases (matched cohort and phase II studies), 50 studies with design limitations (retrospective reviews), 4 supplemental studies (not useful as primary evidence), and 7 meta-analyses. Eight additional studies were included to provide context and were not used to guide recommendations. Well-established RAND-UCLA consensus methodology (modified Delphi) was used to rate the appropriateness of the treatment options. Results: The results of this analysis demonstrate that RT is an effective and safe treatment strategy to reduce the risk of recurrent hypertrophic scars and keloids following surgery in appropriately selected patients. Conclusions: This systematic review provides consensus guidelines for the use of adjuvant RT for the prevention of recurrent hypertrophic scars/keloids based on the available peer-reviewed evidence in the literature.